Presence of nonylphenols in plastic films and their migration into food simulants - Alfirević, Marjetka (Acta chimica slovenica, 2011)
Nonylphenols (NP) possess estrogenic activities and may cause increased risk of cancerous and reproductive abnormalities in several living organisms. Despite their harmful nature, NPs are used as additives in food packaging material, especially plastic, which is the main food contact material in today's packaging landscape. According to the fact that food packaging is one of the major potential food contaminant sources regarding NPs, there is a need for more information on identifying and quantifying of these chemicals when migrating into food. Seventeen plastic films for food packaging were analyzed for the presence of NPs; nine of them were plastic films for deep freeze food packaging. We determined and quantified NPs by Gas Chromatography-Mass Spectrometry (GC-MS) using the internal standard method. All plastic films for deep freeze food packaging contained NPs within a concentration range from 11.9 to 43.7 mg/kg. We also studied the migration of NPs from three of the plastic films for deep freeze food packaging into food simulants. The migration of NPs from these plastic films into 95% ethanol and 10% ethanol was higher than the amount migrating into distilled water or 3% acetic acid.
Keywords: embalaža za hrano; human migration; migracije; migration; nonilfenol; nonulphenols; plastic films